PHENOMENOLOGICAL STUDY: THE EXPERIENCE OF SOCIETY IN DEALING WITH FLOODS BINTARO URBAN VILLAGE DISTRICT OF PESANGGRAHAN SOUTH JAKARTA - Jamaludin, Jamaludin; Widiany Nurrahmah,; Eny Nuraeni Agustin,; Yang Fajar Kurniawan, (Journal of Innovation Research and Knowledge, 2025)
Flood is one of the natural disaster which is frequently happened in Indonesia. Special Capital Region (DKI) of Jakarta has a very high frequency of flood, that requires preparedness. Flood prevention efforts are useful to anticipate losses that ensued and minimize casualties. The experience of citizens against floods have different responses - depending on the disaster preparedness measures undertaken. Aim: this study aims to explore the experience of community preparedness in facing the flood in RT 001 RW 012 Bintaro Urban Village District of South Jakarta Pesanggrahan in 2024. Methode: This study is a qualitative research design of descriptive phenomenology through FGD (Focus Group Discussion) and field notes. The informants are included people who have experienced in flood incident obtained through purposive sampling technique. The data which are collected in the form of FGD recordings, interviews and field notes were analyzed by Colaizzi method. This study identifies four themes, namely: 1) The impact of flooding experienced by the community; 2) Sources of knowledge gained by public about flood prevention programs; 3) Community preparedness efforts in facing the flood; 4) The role of government in the flood disaster preparedness efforts. Result: the results could provide an overview of community preparedness experience in facing the flood. Further research is needed on deeper exploration of the role of nurses in the form of community involvement in flood disaster management. Conclusion: the government's role in dealing with floods, such as dikes, dredging, procurement of pump houses, relocation of settlements, the establishment of flood prevention teams, the availability of public kitchens and logistics, the procurement of flood tools and health services at the local Health Center